STRATEGIES FOR IMPROVING FUNDING OF SCIENCE EDUCATION PROGRAMME IN SECONDARY SCHOOLS FOR SUSTAINABLE DEVELOPMENT IN ABAKALIKI EDUCATION ZONE (Journal of Association of Educational Management and Policy Practitioners, 2024)
This paper focused on the strategies for improving funding of science education programme in secondary schools for sustainable development. It also emphasized on the strategies for improving of funding of science education to include contribution from old school boys, payment of PTA levies by the parent, contribution from school host communities among others. The paper also highlighted on the challenges of funding education. That challenges in funding of education could be traced to policy and strategy instability, inconsistency, inefficient management among others. The paper recommended that government at all level should pay high attention to the education sector for its sustainability. The P.T.A levies should be regularly paid to enable schools provides necessary/minor educational facilities and instructional material for the pupils among others.